Analisis Status Kerusakan Tanah pada Lahan Sawah di Subak Kecamatan Denpasar Utara Berbasis Sistem Informasi Geografis - Krisdianto Putra Sihombing; I Wayan Narka; Ida Bagus Putu Bhayunagiri (Nandur, 2022)
This study aims to determine the status of soil damage, limiting factors, create a map of the status of soil damage, and provide recommendations for repairing soil damage. This research was carried out in Subak, North Denpasar District, from December 2020 to February 2021. The research method was carried out using a survey method, namely observation and soil sampling followed by laboratory analysis. Parameters analyzed were solum thickness, surface kerocks, fraction composition, total porosity, bulk density, electrical conductivity, pH, permeability, and the number of microbes. The results showed that the status of soil damage at the study site was classified as undamaged (N) and lightly damaged (R.I). The undamaged status includes Subak Dalem, Subak Lungatad, Subak Ubung and slightly damaged status includes Subak Kedua, Subak Pakel II, Subak Petangan, Subak Pakel I, Subak Sembung. The limiting factors of the research area are permeability and fraction composition. Recommendations for improvement from the results of the research are the application of Organic-Based Controlled Aerobic Rice Intensification (IPAT-BO) technology, such as the provision of organic matter in the form of rice straw residues and good soil management by plowing the land using cattle or tractor power.